PE Metrics assessing student performance using the national standards & grade-level outcomes for K-12 physical education - Chepko, Stevie; Doan, Robert John; Holt/Hale, Shirley Ann; MacDonald, Lynn Couturier 1959- (SHAPE America, Society of Health and Physical Educators Human Kinetics, 2019)
"Provides assessments that measure student achievement of SHAPE America's Grade-Level Outcomes and thus serves as a companion book for the Standards book and the three SHAPE America Lesson Planning books. Scope--covers most of the elementary grade-level outcomes and samples for middle school and high school plus info on how to create more assessments. Written for K-12 physical education teachers, K-12 physical education administrators and curriculum writers, and PETE students"--